Potensi Pengembangan Olahraga Rekreasi Trekking di Air Terjun Proklamator Lembah Anai Berdasarkan Analisis SWOT - Candra Kirana; Nuridin Widya Pranoto; Anton Komaini; Donal Syafrianto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Recreational trekking is a nature-based physical activity with significant potential to support the development of sport tourism. Proklamator Waterfall in Lembah Anai, Tanah Datar Regency, possesses natural characteristics that are suitable for recreational trekking; however, its management has not yet been optimized. This study aimed to analyze the development potential of recreational trekking at Proklamator Waterfall using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) framework. A qualitative descriptive approach was employed. The participants consisted of one site manager, two local community members, and three visitors selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the destination's main strengths include its well-preserved natural environment, attractive trekking routes, and strong community support. The identified weaknesses are limited financial resources and inadequate supporting facilities and infrastructure. Opportunities arise from the growing interest in nature-based tourism, the expansion of digital media promotion, and community participation, while threats include extreme weather conditions, landslides, slippery trails, and falling trees. Based on the SWOT analysis, the development of recreational trekking at Proklamator Waterfall should focus on improving facilities, strengthening digital promotion, empowering local communities, and enhancing safety management to establish a sustainable sport tourism destination.